Attachment, emotion regulation, and well‐being in couples: Intrapersonal and interpersonal associations - Brandão, Tânia (2019)
Objective: There is a well‐established link in the literature between secure romantic attachment orientation and psychological well‐being. The underlying processes of this link and the couple interplay between attachment and well‐being are notably less explored. Using a dyadic framework, this study examines both couple members' emotion regulation strategies as potential mediators of this link. Method: One hundred and nineteen heterosexual couples completed self‐report measures on attachment style, psychological well‐being, tendency to suppress emotions, and emotion expression. Analyses were performed using the actor–partner interdependence mediation model that distinguishes between intrapersonal and interpersonal influences. Results: Results showed that controlling for relationship length, there was an intrapersonal indirect effect of attachment avoidance on psychological well‐being through emotion suppression. Moreover, interpersonal indirect effects were found (a) with individual attachment avoidance being associated with partner's psychological well‐ being through own emotion expression and (b) individual's attachment anxiety being associated with partner's psychological well‐being through both own's emotion expression and partner's emotion suppression. Conclusions: These findings highlight the complex associations among attachment, emotion regulation, and well‐being and point out the role of emotion regulation as a potential underlying pathway explaining these associations. The results suggest the importance of considering the relational nature of emotional and attachment dynamics in couples.